An economic model of the Los Olivitos mangrove ecosystem in Venezuela - G í¶ran M í¤lerKarl; Aniyar, Sara; Casler, Clark; Weir, Enrique; Fuenmayor, Judith; Rojas, José; Reyes, Jeny (Boletín del Centro de Investigaciones Biológicas)
An economic model that will allow us to analyze different management options for the Los Olivitos mangrove ecosystem, in western Venezuela, is presented. A basic economic problem behind any ecosystem management decision is the allocation of natural resources. It is a matter of making the appropriate “trade-off” between preservation and changes in resource uses. This trade-off requires a value analysis of the variable functions and goods provided by the wetland. The model takes into account the ecological knowledge presently available: and considers eight ecosystem features: S1 = the current stock of mangrove (mangrove biomass), S2 = the fish stock, S3 = a vector which describes all the Los Olivitos characteristics eventually attracting tourists. S4 = carbon sequestration mangrove service, S5 = nutrient stock, S6 = salinity, S7, biodiversity, and A = are above sea level. The different components of the economic value of the ecosystem will be estimated via eight equations.